Searching for Cu, Cd, Zn Bioindicator Species of Macrofauna Benthic in Kangean Archipelago and Surabaya, Indonesia - Aunurohim, Aunurohim (IPTEK The Journal for Technology and Science, 2009)
The comparative study of copper accumulation, cadmium and zinc by macro fauna benthic species has been achieved in the Kangean Archipelago and Sura-baya (Indonesia). The preliminary survey had been taken because of the scientific data did not exist on the metallic contamination in the Kangean Archipelago. In compari-son, Surabaya is an industrial city that presents a strong potential contamination of copper; cadmium and zinc refer to the previous studies. The main object of the re-search was comparing the contamination level of the two sites by the slant concentration measurement on the abun-dant of macro fauna benthic species. It would be possible to define the bio indicator species of the contamination in order to use it as the term on the whole inter tropical cen-tre. The results showed that there was a specific differren-tiation between copper and cadmium concentration for Gafrarium tumidum (Kangean) in a varied sizes; Anadara inadequate collected from Kangean had shown the same variation but not for the cadmium concentration. The va-riances analysis of two factors (size vs site) on Anadara inadequate from both of sites showed that there were spe-cific differentiation between copper and zinc concentra-tion, but not for cadmium. Generally, the contamination level of copper, cadmium and zinc in Surabaya is higher than Kangean. The species of Nassarius globosus, Saccos-trea cucullata, Hinia sp and Anadara inadequate can be used to bioindicator species. The Anadara inadequate spe-cies is an ideal bioindicator species for the surveillance of cadmium contamination because they mostly found in the both of sites and accumulated (in average) strongly with 10,98 - 11,31 Î¼g/g dry weight.